Review of the input-output network and its application in energy and mineral industries - Weidong, Li; Jianwu, Li; Bojie, Wen; Mei, Han (Frontiers in Energy Research, 2022)
Nowadays, it has become a widespread consensus to deal with global warming through carbon emission reduction among mainstream scientists in the world. As the main battlefield and main force to achieve carbon peak and carbon neutrality, the energy and mineral industries play a crucial role. At the same time, as the basic industries provide energy and raw materials, the energy and mineral industries and other industries form a complex and integrated economic system with each other through input-output correlation. It can provide scientific reference for policymakers and market investors to quantitatively reveal the overall structure of the industry and deeply analyze the role and position of energy and mineral industries in it. Combining the input-output analysis with the complex network theory, the input-output network is a set of theoretical methods with strong theory and application to describe the industrial association structure both between economies and within them, and a powerful tool for studying linked character between energy and mineral industries and related industries, carbon emission, environmental protection and so on from the perspective of physical economics. Based on document analysis, this paper introduces the concept and theoretical basis of the input-output network and energy and mineral industries, and then systematically expounds the research status of the input-output network from several dimensions such as data source, research object, and research question. Finally, the paper summarizes research methods, research objects, and application scope of the input-output network, points out the weak links, and prospects some future development directions in energy and mineral industries.